2023
DOI: 10.3390/nu15071696
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Vitamin D in the Intestinal and Respiratory Systems

Abstract: Vitamin D plays a crucial role in modulating the innate immune response by interacting with its intracellular receptor, VDR. In this review, we address vitamin D/VDR signaling and how it contributes to the regulation of intestinal and respiratory microbiota. We additionally review some components of the innate immune system, such as the barrier function of the pulmonary and intestinal epithelial membranes and secretion of mucus, with their respective modulation by vitamin D. We also explore the mechanisms by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 191 publications
0
2
0
Order By: Relevance
“…In particular, the vitamin D/VDR complex is known to modulate both the way in which pathogens are recognized (e.g., by influencing the pathogen recognition receptors) and the host's responses (e.g., NF-kB-and IL1β-driven downstream responses). In addition to directly regulating the transcription of cathelicidins and defensins, the vitamin D/VDR complex is also able to regulate the cytosolic components of the pathogen recognition system, such as the inflammasome-driven response [103,111].…”
Section: Vitamin D and Immunity Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…In particular, the vitamin D/VDR complex is known to modulate both the way in which pathogens are recognized (e.g., by influencing the pathogen recognition receptors) and the host's responses (e.g., NF-kB-and IL1β-driven downstream responses). In addition to directly regulating the transcription of cathelicidins and defensins, the vitamin D/VDR complex is also able to regulate the cytosolic components of the pathogen recognition system, such as the inflammasome-driven response [103,111].…”
Section: Vitamin D and Immunity Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…Vitamin D plays a significant role in most physiologic and pathologic processes in the body, including DNA repair mechanisms, the prevention of cancer cell proliferation, lowering viral replication rates, antimicrobial defenses, lowering pro-inflammatory cytokine concentrations, the balance of the microbiota, innate and adaptive immune system homeostasis, and gene expression [35,[39][40][41]. A 2019 randomized controlled double-blind clinical trial (RCT) demonstrated a dose-dependent relationship between vitamin D3 supplementation and gene expression, showing the up-or down-regulation of 1289 identified genes with the daily supplementation of 10,000 IU/day compared to 320 genes with the supplementation of 4000 IU/day and 162 genes with the supplementation of 600 IU/day [42].…”
Section: Vitamin D Overviewmentioning
confidence: 99%